2017
DOI: 10.1016/j.sdentj.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the influence of gender and skin color on the preference of tooth shade in Saudi population

Abstract: Gender and skin color influences the perception of teeth shades among general population. Therefore, lighter tooth shades (BL1, BL2) for lighter skin color and comparatively darker tooth shades (BL4, B1, A1) for darker skin individuals should be prescribed as these are perceived as natural among Saudi population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 17 publications
1
20
1
2
Order By: Relevance
“…This came in disagreement with previous studies that reported that while most of the participants preferred the whitest teeth in fair skin shades, in dark skin shades the less white tooth shades were the most preferred. 17,18,20 This difference could be related to the range of tooth shades used in the previous studies; in this study tooth shades from the VITA 3D Master shade guide which represent shades commonly seen in natural teeth were used, but previous studies used a bleached tooth shade guide or artificially whitened tooth shades in addition to the natural tooth shades. 17,18,20 Online survey offers several advantages for researchers as it is a very effective tool for fast data collection and enables researchers to approach participants from across the world.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This came in disagreement with previous studies that reported that while most of the participants preferred the whitest teeth in fair skin shades, in dark skin shades the less white tooth shades were the most preferred. 17,18,20 This difference could be related to the range of tooth shades used in the previous studies; in this study tooth shades from the VITA 3D Master shade guide which represent shades commonly seen in natural teeth were used, but previous studies used a bleached tooth shade guide or artificially whitened tooth shades in addition to the natural tooth shades. 17,18,20 Online survey offers several advantages for researchers as it is a very effective tool for fast data collection and enables researchers to approach participants from across the world.…”
Section: Discussionmentioning
confidence: 97%
“…A more clinically applicable study evaluated a specific population preference of tooth shade using a commercially available A-D Shade guide to construct computer-modified images. 20 It showed that most of the study participants (83.7%) preferred lighter tooth shade for lighter skin shades, and darker tooth shade for darker skin. 20 However, the findings of this study cannot be generalized to other populations, since cultural and ethnical background could influence individuals' perception of smile attractiveness.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Esta diferencia en la percepción de las discrepancias de las sonrisas debe tenerse en cuenta durante las fases finales del tratamiento de ortodoncia y la restauración de los dientes anteriores en pacientes marroquíes. Labban et al (2017) (16) evaluaron la influencia del género y el color de la piel en la preferencia de los diferentes tonos de dientes en la población general. Se manipularon dos fotografías estandarizadas de sonrisa frontal de sujetos masculinos y femeninos utilizando photoshop para representar 4 colores de piel [(tipo II, III, IV y V) (escala de Fitzpatrick)].…”
Section: Ousehala Et Al (2016)unclassified
“…Así mismo, la cultura y los medios de comunicación influyen en cómo se juzga una sonrisa (18) ; variando la percepción de algunos de estos parámetros en cada realidad local. Cabe tener en cuenta, que el instrumento que se utiliza para medir la percepción es la escala visual análoga (EVA); la cual, es bastante subjetiva; sin embargo, es la más utilizada (8,11,14,16) .…”
Section: Ousehala Et Al (2016)unclassified